Overexpression and prognostic significance of p53 in Basal Cell Carcinoma, Squamous cell Carcinoma and Malignant Melanoma of the Skin - Javeed, Saira (International Journal of Pathology, 2020)
Objective: To evaluate the immunohistochemical overexpression of p53 in basal cell carcinoma squamous cell carcinoma, collectively known as non-melanoma skin cancer and malignant melanoma of skin in the local population and determine its prognostic significance. Methods: It was a descriptive cross-sectional study conducted in the Pathology Department of Pakistan Institute of Medical Sciences, Islamabad. All skin biopsies received in the pathology department and diagnosed as basal cell carcinoma, squamous cell carcinoma and malignant melanoma were included in the study. 55 skin cancers were included which comprises of 61.8% basal cell carcinoma, 25.5% squamous cell carcinoma and 12.7% malignant melanoma. p53 overexpression was evaluated by immunohistochemistry and the results were analyzed by using SPSS version 21. A p-value <0.05 was considered significant. Results: p53 over expression was seen in 82.3% of basal cell carcinoma, 50% of squamous cell carcinoma while none was seen in malignant melanoma. (p value <0.001). 55.8% cases of basal cell carcinoma showed strong staining, 20.5% had moderate staining and 5.8% had weak staining pattern. Squamous cell carcinoma showed strong (57.1%) and moderate (42.8%) staining pattern. A significant correlation between p53 over expression and the tumor size of both basal and squamous cell carcinoma was observed (p value 0.001) Conclusion: Majority of the squamous and basal cell carcinomas expressed p53 over expression with an important prognostic implication. Complete absence of p53 in malignant melanoma suggests another carcinogenic pathway not involving gene p53 mutation. Key words:,